2011
DOI: 10.3168/jds.2010-3547
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effect of altering nutrition and nutritional strategies in early lactation on reproductive performance and estrous behavior of high-yielding Holstein-Friesian dairy cows

Abstract: Reproductive performance in the high-yielding dairy cow has severely decreased in the last 40 yr. The aim of this study was to compare the effectiveness of 4 nutritional strategies in improving the reproductive performance of high-yielding dairy cows. It was hypothesized that offering cows a high-starch ration in early lactation would enhance the onset of luteal activity, and that decreasing the severity of negative energy balance in the early postcalving period would improve reproductive parameters. Nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 62 publications
3
30
2
2
Order By: Relevance
“…The lower reproductive performance of mature cows was expected; however, the pregnancy ratio even in the younger cows was considered unsatisfactory, because more than half of the cows in this herd did not reach a 15-month maximum recommended calving interval (De Vries, 2006). For instance, Gilmore et al (2011) found pregnancy rates of 71.4% at 100 days, well above the results of the present study. Santos et al (2009) also observed higher conception rates on day 58 after artificial insemination on primiparous than multiparous cows -37.5% vs. 29.7%, respectively -confirming our finding that younger animals have better reproduction.…”
Section: Discussionsupporting
confidence: 76%
“…The lower reproductive performance of mature cows was expected; however, the pregnancy ratio even in the younger cows was considered unsatisfactory, because more than half of the cows in this herd did not reach a 15-month maximum recommended calving interval (De Vries, 2006). For instance, Gilmore et al (2011) found pregnancy rates of 71.4% at 100 days, well above the results of the present study. Santos et al (2009) also observed higher conception rates on day 58 after artificial insemination on primiparous than multiparous cows -37.5% vs. 29.7%, respectively -confirming our finding that younger animals have better reproduction.…”
Section: Discussionsupporting
confidence: 76%
“…In subsequent research, the number of cows pregnant at 120 days was greater for cows fed a glucogenic (high-starch) diet that increased insulin early postpartum followed by the lipogenic diet (higher fat) during the breeding period (Garnsworthy et al, 2009). More recent studies have not confirmed this effect (Dyck et al, 2011;Gilmore et al, 2011) although diets and experimental conditions differed and cow numbers were limited. The aim to increase early postpartum insulin by feeding higher starch diets must be tempered by the need to maintain optimal rumen health and digestion.…”
Section: Postpartum (Fresh Cow) Dietary Considerationsmentioning
confidence: 95%
“…The intensity of oestrous behaviour expression is not only important for successful artificial insemination but also for high conception and calving rates once inseminated. Several studies have shown that cows with a more intense oestrous behaviour (including the standing response) have higher conception and calving rates (Dransfield et al, 1998;Garcia et al, 2011;Gilmore et al, 2011). Oestrous behaviour is thus a key fertility trait in cows.…”
Section: Introductionmentioning
confidence: 99%